CAT teaching practices: an international survey - Zhang, Xiaochun; Nunes Vieira, Nunes (The Journal of Specialised Translation, 2021)
This article analyses the way CAT teaching is carried out in higher education institutions, based on the findings of a survey distributed to CAT tool teachers from around the world. The survey was set up on Typeform, an online survey platform, and remained open from 15 December 2017 to 15 December 2018. We received 120 responses by 102 participants from 112 institutions in 33 countries and regions. The findings suggested that tutorials, where students are told how to operate a CAT tool, were the most prevalent teaching method, although some learning-by-doing activities were adopted. The survey results also indicated that CAT tool training should be linked more closely to practical translation sessions and could be more intellectually stimulating. These results call for a wider debate on the status of CAT in the translation curriculum and on how it should integrate with other subjects. More empirical research is also required to examine integrated teaching methods that make it easier to stimulate competent use of translation technologies as well as their broader conceptual implications.